2006
DOI: 10.5194/acp-6-1485-2006
|View full text |Cite
|
Sign up to set email alerts
|

Mixing height determination by ceilometer

Abstract: Abstract.A novel method for estimating the mixing height based on ceilometer measurements is described and tested against commonly used methods for determining mixing height. In this method an idealised backscatter profile is fitted to the observed backscatter profile. The mixing height is one of the idealised backscatter profile parameters.An extensive amount of ceilometer data and vertical soundings data from the Helsinki area in 2002 is utilized to test the applicability of the ceilometer for mixing height … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
128
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(133 citation statements)
references
References 27 publications
5
128
0
Order By: Relevance
“…The KED estimation error is a tool that can help to guide the installation of future instrumentation. A particularly promising data set can be obtained from lidars or ceilometers, that are able to continuously observe aerosol backscatter signals, from which MH can be retrieved at relatively low cost (Eresmaa et al, 2006). Networks of lidars and ceilometers are already operated throughout Europe (Haeffelin et al, 2012).…”
Section: Additional Mh Datamentioning
confidence: 99%
“…The KED estimation error is a tool that can help to guide the installation of future instrumentation. A particularly promising data set can be obtained from lidars or ceilometers, that are able to continuously observe aerosol backscatter signals, from which MH can be retrieved at relatively low cost (Eresmaa et al, 2006). Networks of lidars and ceilometers are already operated throughout Europe (Haeffelin et al, 2012).…”
Section: Additional Mh Datamentioning
confidence: 99%
“…Apart from a few occasions (e.g., André and Mahrt, 1982;Berman et al, 1999;Day et al, 2010), NSL measurements are particularly uncommon since most radiosonde launches are performed during daytime ML hours. In recent years, remote-sensing techniques such as light detection and ranging (lidar), radio acoustic sounding systems (RASS), and sonic detection and ranging (sodar) systems have allowed for the continuous monitoring of the BL (Cohn and Angevine, 2000;Schäfer et al, 2011;Seibert et al, 2000;Emeis et al, 2004Emeis et al, , 2006Emeis et al, , 2012Eresmaa et al, 2006;Baars et al, 2008;McKendry et al, 2009;Muñoz and Undurraga, 2010;Haman et al, 2012;Milroy et al, 2012;Compton et al, 2013;Scarino et al, 2014;Wiegner and Gasteiger, 2015;Uzan et al, 2016). Ceilometers in particular offer a low-maintenance and low-cost solution to constantly monitoring the ML using aerosol backscatter while also facilitating the monitoring of the nocturnal stable layer, internal aerosol layers, and the nighttime residual layer (Haman et al, 2012Pandolfi et al, 2013;Peña et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Even then the presence of multiple aerosol layers, or absence of a strong contrast at the top of the mixed layer, may preclude mixing height detection using lidar. For example, during the deployment of a monostatic ceilometer, Eresmaa et al (2006) found that boundary layers below 140 m were undetectable. In such cases, an alternative method entirely needs to be sought.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%